Determining minimum visibility levels in different road lighting scenarios. (November 2018) - Buyukkinaci, B; Onaygil, S; Guler, O; Yurtseven, MB
This study investigates visibility levels for different road lighting scenarios. Four different road lighting classes (M2, M3, M4, M5), two different colour temperature luminaires (4000 K and 6000 K) and four different critical object reflectances (0.20, 0.30, 0.40, 0.50) were used to determine the effects of lighting classes and colour temperatures on the critical object detection. In total, 1920 photographs were taken on a test road and visibility levels were calculated for each case. From these 1920 visibility levels, photographs corresponding to 245 visibility level values ranging from 1 to 9 were selected and evaluated by 30 subjects aged between 25 and 35 years in a laboratory environment. As a result of the study, it was shown that visibility levels are between 7.0 and 8.5 for road lighting classes ranging from M2 to M5, illuminated by light sources with different colour temperatures, for 100% detection of critical objects. This result is in line with the suggested VL values changing between 7 and 10 in the literature.